Convict/Aboriginal partnerships and ruptured histories in The Nightingale. Issue 1 (2nd January 2020) - Findlay, James
ABSTRACT: This article considers the convict/Aboriginal partnership at the heart of Jennifer Kent's The Nightingale . In doing so it locates Clare and Billy's relationship within a broader representational history of convict/Aboriginal partnerships on screen. It explores how The Nightingale conforms to, or ruptures, the narrative patterns and tropes that have developed around such encounters. Furthermore, it considers the partnership's revisionist potential and continuing limitations as a representational means to exploring the multi-layers of power, violence and colonisation on screen.